Thompson & Thompson genetics in medicine - Nussbaum, Robert L.; McInnes, Roderick R. ;Willard, Huntington F. (Philadelphia, Pennsylvania : Elsevier Science, 2016)
Updated to reflect the newest changes in genetics, Thompson & Thompson's genetics in medicine returns as one of the most favored texts in this fascinating and rapidly evolving field. By integrating the classic principles of human genetics with modern molecular genetics, this medical reference book utilizes a variety of learning tools to help you understand a wide range of genetic disorders. Acquire the state-of-the-art knowledge you need on the latest advances in molecular diagnostics, the Human Genome Project, pharmacogenetics, and bio-informatics. Better understand the relationship between basic genetics and clinical medicine with a variety of clinical case studies. Recognize a wide range of genetic disorders with visual guidance from more than 240 dynamic illustrations and high-quality photos. Immerse yourself in updated graphics, full-color text, illustrations, line diagrams, and clinical photos of genetic diseases. Explore the latest genetic content available in order to remain up to date on the most current trends in the field. Take advantage of a double-page clinical case study section that demonstrates and reinforces general principles of disease inheritance, pathogenesis, diagnosis, management, and counseling . Enhance your critical thinking skills and better retain information. Each chapter ends with up to 5 quick genetic "problems" related to what has just been reviewed, with answers provided in the back of the book.
Introduction -- Introduction to the human genome -- The human genome: gene structure and function -- Human genetic diversity: mutation and polymorphism -- Principles of clinical cytogenetics and genome analysis -- The chromosomal and genomic basis of disease: disorders of the autosomes and sex chromosomes -- Patterns of single-gene inheritance -- Complex inheritance of common multifactorial disorders -- Genetic variation in populations -- Identifying the genetic basis for human disease -- The molecular basis of genetic disease : general principles and lessons from the hemoglobinopathies -- The molecular, biochemical, and cellular basis of genetic disease -- The treatment of genetic disease -- Developmental genetics and birth defects -- Cancer genetics and genomics -- Risk assessment and genetic counseling -- Prenatal diagnosis and screening -- Application of genomics to medicine and personalized health care -- Ethical and social issues in genetics and genomics.
Includes bibliographical references and index.
Keywords: MEDICAL GENETICS